Spontaneous Septic Arthritis of Pubic Symphysis in an Elite Athlete - F. Jasmijn Smits; Herman Frima; Christoph Schaeffeler; Christoph Sommer (Case Reports in Surgery)
Septic arthritis of the pubic symphysis is a potentially severe disease. Athletes are at risk of this form of spontaneous arthritis, as inflammation of the pubic bone due to muscular stress is relatively common. Oedema due to inflammation might predispose to infection through bacteraemia or local bacterial translocation. Suspicion should be raised when an athlete complains of groin pain and has signs of infection (i.e., fever, elevated white blood cell count, and elevated C-reactive protein). Diagnosis is made by imaging showing signs of inflammation combined with positive (blood) cultures. Broad spectrum antibiotics should be started upon suspicion and adjusted according to cultures. An abscess causing clinical deterioration under antibiotic treatment is an indication for invasive intervention (i.e., surgical or image-guided drainage). This is the first case of spontaneous septic arthritis of the pubic symphysis in an athlete requiring surgical and additional image-guided drainage.